Needs of people with rare diseases that can be supported by electronic resources: a scoping review - Jeffrey Braithwaite; John Christodoulou; Stephanie Best; Janet C Long; Bróna Nic Giolla Easpaig; Sarah Hatem; Zoe Fehlberg (BMJ Open, 2022)
Objectives Rare diseases are characterised by low incidence, often with little evidence for effective treatments. Isolated patients and specialist centres for rare diseases are increasingly connected, thanks to the internet. This scoping review aimed to identify issues facing people with a rare disease that authors report may be addressed by electronic resources (mobile applications, websites, social media platforms, telehealth and online portals).Design Scoping review guided by the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines.Data sources Medline, Embase and PsycInfo were searched, supplemented by hand searches of selected journals, in July 2021.Eligibility criteria Peer-reviewed literature in English was searched using terms for rare disease (incidence <1:2000), electronic modalities (eg, mobile phone) and patient support terms. No date limit was set. Conference abstracts were included.Data extraction and synthesis Data extracted: rare disease/group of diseases, name of the e-resource, need identified in the patient cohort, features of the e-resource, any other findings or observations of interest. From this, a framework was developed synthesising features across diseases and resources.Results Seventy-two papers were found (from 383). Fifty-six electronic resources were described in 64 papers, while 12 papers were exploratory studies. Cystic fibrosis (n=28) was the most frequently addressed, followed by haemophilia (n=16).Four domains and 23 subdomains of needs were extracted from the papers. The domains of needs were: support for self-management, access to high-quality information, access to appropriate specialist services, and social support. Subdomains are sometimes related to needs of individual rare diseases (eg, social isolation due to infection risk in people with cystic fibrosis). Fifteen electronic resources were identified that supported parents of children with rare disorders.Conclusions While it can be argued that rare diseases, per se, may be no less distressing or onerous to care for than a high prevalence disease, rare diseases have unique features: the lengthy odyssey to find a diagnosis, then appropriate specialists, the lack of evidence around effective treatments, guidelines or access to knowledgeable general health service providers. Designers of electronic resources are urged to consult key stakeholders to enhance the effectiveness and usability of resources for people with a rare disease.